THE EFFECT OF BRAND AWARENESS AND BRAND IMAGE ON THE PURCHASE DECISION OF KENZO HEALTHY BREAD - Juventius Wahyu Utama; Hilman Farizi (Jurnal Ekonomika dan Bisnis, 2022)
This study analyze the effect of brand awareness and brand image on purchasing decisions for Kenzo's healthy bread. The method in this study uses quantitative research. Then tested using several tests such as validity, reliability, classical assumptions and hypothesis testing using SPSS. The population in this study were all consumers of Kenzo's healthy bread. Sampling was carried out using non-probability sampling with a convenience sampling technique of 106 respondents. The results showed that brand awareness and brand image had an effect on purchasing decisions with an Adjusted R Square value of 0.341 or 34.1%, meaning that the variation of the independent variables used in the model, namely brand awareness (X1) and brand image (X2) of 34.1%, the dependent variable purchasing decision. While the remaining 65.9% is influenced by other factors outside the variables studied. Brand awareness has a positive and significant effect on purchasing decisions for Kenzo's healthy bread. Based on the results of data processing, brand image has a positive and significant effect on purchasing decisions for Kenzo's healthy bread. Based on the results of data processing, brand image and brand awareness simultaneously have a positive and significant effect on purchasing decisions for Kenzo's healthy bread.